A familiarization protocol facilitates the participation of children with asd in electrophysiological research - Turcios, Jacqueline; Cook, Barbara; Irwin, Julia; Rispoli, Taylor; Landi, Nicole (JoVE (Journal of Visualized Experiments), 2017)
This paper includes a detailed description of a familiarization protocol, which is used as an integral component of a larger research protocol to collect electroencephalography (EEG) data and Event-Related Potentials (ERPs). At present, the systems available for the collection of high-quality EEG/ERP data make significant demands on children with developmental disabilities, such as those with an Autism Spectrum Disorder (ASD). Children with ASD may have difficulty adapting to novel situations, tolerating uncomfortable sensory stimuli, and sitting quietly. This familiarization protocol uses Evidence-Based Practices (EBPs) to increase research participants' knowledge and understanding of the specific activities and steps of the research protocol. The tools in this familiarization protocol are a social narrative, a visual schedule, the Premack principle, role-playing, and modeling. The goal of this familiarization protocol is to increase understanding and agency and to potentially reduce anxiety for child participants, resulting in a greater likelihood of the successful completion of the research protocol for the collection of EEG/ERP data.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/080-947-783-936-351, pop00167 tex.type: [object Object]
Keywords: dept.cmd; dept.psy

Personality, Emotional Qualities of Leisure, and Subjective Well-Being in the Elderly. - Kahlbaugh, Patricia; Huffman, Loreen (International journal of aging & human development, 2017)
In this study, we examined personality traits of older adults and their emotional experiences associated with engaging in specific leisure activities. Older individuals (17 males, 32 females), ages ranging from 65 to 97 years (mean age 74), completed measures of Big Five personality traits, positive and negative affect, subjective well-being (SWB), independent functioning, and an emotion-activity inventory. As expected, Extraversion, Agreeableness, Conscientiousness, and Openness to experience were related to positive affect, while Neuroticism was related to negative affect. Openness and Agreeableness were related to positive emotions experienced in social and cognitive domains, and Agreeableness was related to greater SWB, greater positive affect, and more positively experienced activities. Neuroticism was related to lower SWB and fewer positively experienced activities. These findings suggest that assessing the fit between personality and emotions experienced during activities should be considered when creating programs tailored to elderly individuals, with the goal of encouraging more active and rewarding lives.
17 citations (Crossref) [2023-10-31] Place: United States Kahlbaugh, Patricia. 1 Psychology Department, Southern Connecticut State University, New Haven, CT, USA. Huffman, Loreen. 2 Psychology Department, Missouri Southern State University, Joplin, MO, USA.
Keywords: *Aging/px [Psychology]; *Emotions; *Leisure Activities; *Personal Satisfaction; *Personality; Affect; Aged; Aged; 80 and over; Aging; Emotions; Female; Humans; Leisure Activities; Male; Personal Satisfaction; Personality; affect; aged; aging; dept.psy; emotion; emotions; female; human; leisure; male; personality; psychology; satisfaction; subjective well-being; successful aging; very elderly

Restraint stress enhances alcohol intake in adolescent female rats but reduces alcohol intake in adolescent male and adult female rats. - Wille-Bille, Aranza; Ferreyra, Ana; Sciangula, Martina; Chiner, Florencia; Nizhnikov, Michael E; Pautassi, Ricardo Marcos (Behavioural brain research, 2017)
Adolescents may be more sensitive to stress-induced alcohol drinking than adults, which would explain the higher prevalence of alcohol abuse and dependence in late adolescence than in adulthood. The present study analyzed the impact of restraint stress on the initiation of alcohol intake across 2 weeks of intermittent, two-bottle choice intake in male and female adolescent rats and adult female rats. Restraint stress significantly increased alcohol intake and preference in female adolescent rats but decreased alcohol intake and preference in male adolescent and female adult rats. The effects of restraint stress on alcohol intake were mitigated in adolescent females following administration of the kappa opioid receptor antagonist norbinaltorphimine. Adolescent but not adult female rats that were subjected to restraint stress spent more time on the open arms of the elevated plus maze. Female adolescents exposed to stress also exhibited greater risk-taking behaviors in a concentric square field test compared with non-stressed controls. These results indicate age- and sex-related differences in the sensitivity to alcohol-stress interactions that may facilitate the initiation of alcohol use in female adolescents. The facilitatory effect of stress on alcohol intake was related to greater exploratory and risk-taking behaviors in young females after stress exposure. Copyright © 2017 Elsevier B.V. All rights reserved.
42 citations (Crossref) [2023-10-31] Place: Netherlands Wille-Bille, Aranza. Instituto de Investigacion Medica M. y M. Ferreyra (INIMEC-CONICET), Universidad Nacional de Cordoba, Cordoba, CP 5000, Argentina. Ferreyra, Ana. Instituto de Investigacion Medica M. y M. Ferreyra (INIMEC-CONICET), Universidad Nacional de Cordoba, Cordoba, CP 5000, Argentina; Facultad de Psicologia, Universidad Nacional de Cordoba, Cordoba, CP 5000, Argentina. Sciangula, Martina. Instituto de Investigacion Medica M. y M. Ferreyra (INIMEC-CONICET), Universidad Nacional de Cordoba, Cordoba, CP 5000, Argentina; Facultad de Psicologia, Universidad Nacional de Cordoba, Cordoba, CP 5000, Argentina. Chiner, Florencia. Instituto de Investigacion Medica M. y M. Ferreyra (INIMEC-CONICET), Universidad Nacional de Cordoba, Cordoba, CP 5000, Argentina; Facultad de Psicologia, Universidad Nacional de Cordoba, Cordoba, CP 5000, Argentina. Nizhnikov, Michael E. Department of Psychology, Southern Connecticut State University, United States. Pautassi, Ricardo Marcos. Instituto de Investigacion Medica M. y M. Ferreyra (INIMEC-CONICET), Universidad Nacional de Cordoba, Cordoba, CP 5000, Argentina; Facultad de Psicologia, Universidad Nacional de Cordoba, Cordoba, CP 5000, Argentina. Electronic address: rpautassi@gmail.com.
Keywords: *Aging/ph [Physiology]; *Aging/px [Psychology]; *Alcohol Drinking/pp [Physiopathology]; *Alcohol Drinking/px [Psychology]; *Sex Characteristics; *Stress; Psychological/pp [Physiopathology]; Adolescents; Adults; Age differences; Aging; Aging/de [Drug Effects]; Alcohol; Alcohol Drinking; Alcohol Drinking/dt [Drug Therapy]; Animals; Article; Central Nervous System Depressants; Central Nervous System Depressants/ad [Administration & Dosage]; Choice Behavior; Choice Behavior/de [Drug Effects]; Choice Behavior/ph [Physiology]; Disease Models; Animal; Ethanol; Ethanol/ad [Administration & Dosage]; Exploratory Behavior; Exploratory Behavior/de [Drug Effects]; Exploratory Behavior/ph [Physiology]; Female; Male; Motor Activity; Motor Activity/de [Drug Effects]; Motor Activity/ph [Physiology]; Naltrexone; Naltrexone/aa [Analogs & Derivatives]; Naltrexone/pd [Pharmacology]; Narcotic Antagonists; Narcotic Antagonists/pd [Pharmacology]; Rats; Wistar; Receptors; Opioid; kappa; Receptors; Opioid; kappa/ai [Antagonists & Inhibitors]; Receptors; Opioid; kappa/me [Metabolism]; Restraint; Physical; Risk-Taking; Sex Characteristics; Stress; Stress; Psychological; Stress; Psychological/dt [Drug Therapy]; Wistar rat; [kappa] opioid receptors; adolescent; adult; age; aging; alcohol; alcohol consumption; analogs and derivatives; animal; animal experiment; antagonists and inhibitors; behavior assessment; central depressant agent; comparative study; concentric square field test; controlled study; decision making; dept.psy; disease model; drinking behavior; drug effects; drug therapy; elevated plus maze test; exercise; experimental study; exploratory behavior; exploratory behavior test; female; high risk behavior; immobilization stress; kappa opiate receptor; kappa opiate receptor antagonist; male; mental stress; metabolism; motor activity; naltrexone; narcotic antagonist; nonhuman; norbinaltorphimine

Electrophysiological Indices of Audiovisual Speech Perception in the Broader Autism Phenotype. - Irwin, Julia; Avery, Trey; Turcios, Jacqueline; Brancazio, Lawrence; Cook, Barbara; Landi, Nicole (Brain sciences, 2017)
When a speaker talks, the consequences of this can both be heard (audio) and seen (visual). A novel visual phonemic restoration task was used to assess behavioral discrimination and neural signatures (event-related potentials, or ERP) of audiovisual processing in typically developing children with a range of social and communicative skills assessed using the social responsiveness scale, a measure of traits associated with autism. An auditory oddball design presented two types of stimuli to the listener, a clear exemplar of an auditory consonant-vowel syllable /ba/ (the more frequently occurring standard stimulus), and a syllable in which the auditory cues for the consonant were substantially weakened, creating a stimulus which is more like /a/ (the infrequently presented deviant stimulus). All speech tokens were paired with a face producing /ba/ or a face with a pixelated mouth containing motion but no visual speech. In this paradigm, the visual /ba/ should cause the auditory /a/ to be perceived as /ba/, creating an attenuated oddball response; in contrast, a pixelated video (without articulatory information) should not have this effect. Behaviorally, participants showed visual phonemic restoration (reduced accuracy in detecting deviant /a/) in the presence of a speaking face. In addition, ERPs were observed in both an early time window (N100) and a later time window (P300) that were sensitive to speech context (/ba/ or /a/) and modulated by face context (speaking face with visible articulation or with pixelated mouth). Specifically, the oddball responses for the N100 and P300 were attenuated in the presence of a face producing /ba/ relative to a pixelated face, representing a possible neural correlate of the phonemic restoration effect. Notably, those individuals with more traits associated with autism (yet still in the non-clinical range) had smaller P300 responses overall, regardless of face context, suggesting generally reduced phonemic discrimination.
8 citations (Crossref) [2023-10-31] Place: Switzerland Irwin, Julia. Haskins Laboratories, New Haven, CT 06511, USA. julia.irwin@yale.edu. Irwin, Julia. Department of Psychology, Southern Connecticut State University, New Haven, CT 06515, USA. julia.irwin@yale.edu. Avery, Trey. Haskins Laboratories, New Haven, CT 06511, USA. trey.avery@yale.edu. Turcios, Jacqueline. Haskins Laboratories, New Haven, CT 06511, USA. jacqueline.turcios@yale.edu. Turcios, Jacqueline. Department of Communication Disorders, Southern Connecticut State University, New Haven, CT 06515, USA. jacqueline.turcios@yale.edu. Brancazio, Lawrence. Haskins Laboratories, New Haven, CT 06511, USA. brancaziol1@southernct.edu. Brancazio, Lawrence. Department of Psychology, Southern Connecticut State University, New Haven, CT 06515, USA. brancaziol1@southernct.edu. Cook, Barbara. Department of Communication Disorders, Southern Connecticut State University, New Haven, CT 06515, USA. cookb5@southernct.edu. Landi, Nicole. Haskins Laboratories, New Haven, CT 06511, USA. nicole.landi@yale.edu. Landi, Nicole. Psychological Sciences, University of Connecticut, Storrs, CT 06269, USA. nicole.landi@yale.edu.
Keywords: Article; Audiovisual speech perception; Broader autism phenotype; Development; ERP; audiovisual aid; audiovisual equipment; audiovisual speech perception; autism; behavior; broader autism phenotype; child; clinical article; dept.cmd; dept.hls; dept.psy; development; electrophysiology; female; human; male; participant observation; phenotype; social adaptation; social competence; speech perception; stimulus; vision test

Electrophysiology of perception and processing of phonological information as indices of toddlers' language performance - Harwood, Vanessa; Preston, Jonathan; Grela, Bernard; Roy, Dooti; Harold, Olivia; Turcios, Jacqueline; Andrada, Kiyomi; Landi, Nicole (Journal of Speech Language and Hearing Research, 2017)
Purpose: The toddler years are a critical period for language development and growth. We investigated how event-related potentials (ERPs) to repeated and novel nonwords are associated with clinical assessments of language in young children. In addition, nonword repetition (NWR) was used to measure phonological working memory to determine the unique and collective contribution of ERP measures of phonemic discrimination and NWR as predictors of language ability. Method: Forty children between the ages of 24-48 months participated in an ERP experiment to determine phonemic discrimination to repeated and novel nonwords in an old/new design. Participants also completed a NWR task to explore the contribution of phonological working memory in predicting language. Results: ERP analyses revealed that faster responses to novel stimuli correlated with higher language performance on clinical assessments of language. Regression analyses revealed that an earlier component was associated with lower level phonemic sensitivity, and a later component was indexing phonological working memory skills similar to NWR. Conclusion: Our findings suggest that passive ERP responses indexing phonological discrimination and phonological working memory are strongly related to behavioral measures of language.
Citation Key Alias: lens.org/016-284-901-764-293 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Brain; Child Language; Child; Preschool; Discrimination (Psychology); Electroencephalography; Evoked Potentials; Female; Humans; Language Tests; Male; Memory; Short-Term; Pattern Recognition; Physiological; Phonetics; Reaction Time; Regression Analysis; Signal Processing; Computer-Assisted; Speech Perception; adult; brain; child; clinical article; dept.psy; electroencephalography; event related potential; evoked response; female; human; language ability; language development; language test; male; pattern recognition; perception; perceptive discrimination; phonetics; physiology; preschool child; reaction time; regression analysis; short term memory; signal processing; speech perception; stimulus; working memory; young adult; ⚠️ Invalid DOI

EdPsych modules - Durwin, Cheryl Cisero; Reese-Weber, Marla J. (SAGE Publications, Inc, 2017)
Now with SAGE Publications, Cheryl Cisero Durwin and Marla Reese-Weber’s EdPsych Modules uses an innovative implementation of case studies and a modular format to address the challenge of effectively connecting theory and research to practice. Each module is a succinct, stand-alone topic that represents every subject found in traditional chapter texts and can be used in any order for maximum flexibility in organizing your course. Each of the book’s eight units of modules begins with a set of four case studies–early childhood, elementary, middle school, and secondary–and ends with "Assess" and "Reflect and Evaluate" questions and activities to encourage comprehension and application of the research and theories presented. The case approach and the extensive pedagogy that support it allows students to constantly see the applications of the theories and research that they are studying in the text.
Keywords: dept.psy

The development of gaze to a speaking face. - Irwin, Julia; Brancazio, Lawrence; Volpe, Nicole (The Journal of the Acoustical Society of America, 2017)
When a speaker talks, the visible consequences of what they are saying can be seen. Listeners are influenced by this visible speech both in a noisy listening environment and even when auditory speech can easily be heard. While visible influence on heard speech has been reported to increase from early to late childhood, little is known about the mechanism that underlies this developmental trend. One possible account of developmental differences is that looking behavior to the face of a speaker changes with age. To examine this possibility, the gaze to a speaking face was examined in children from 5 to 10 yrs of age and adults. Participants viewed a speaker's face in a range of conditions that elicit looking: in a visual only (speech reading) condition, in the presence of auditory noise (speech in noise) condition, and in an audiovisual mismatch (McGurk) condition. Results indicate an increase in gaze on the face, and specifically, to the mouth of a speaker between the ages of 5 and 10 for all conditions. This change in looking behavior may help account for previous findings in the literature showing that visual influence on heard speech increases with development.
3 citations (Crossref) [2023-10-31] Place: United States Irwin, Julia. Haskins Laboratories, 300 George Street, New Haven, Connecticut 06511, USA. Brancazio, Lawrence. Southern Connecticut State University, 501 Crescent Street, New Haven, Connecticut 06515, USA. Volpe, Nicole. Southern Connecticut State University, 501 Crescent Street, New Haven, Connecticut 06515, USA.
Keywords: *Facial Expression; *Fixation; Ocular; *Speech Acoustics; *Speech Perception; *Visual Perception; *Voice Quality; Acoustic Stimulation; Acoustics; Age Factors; Audiometry; Speech; Child; Child; Preschool; Cues; Early-to-late; Facial Expression; Female; Fixation; Ocular; Humans; Male; Noise; Noise/ae [Adverse Effects]; Perceptual Masking; Photic Stimulation; Physics; Speech; Speech Acoustics; Speech Perception; Speech in noise; Speech reading; Video Recording; Visible speech; Visual Perception; Voice Quality; Young Adult; age; association; auditory stimulation; child; dept.hls; dept.psy; eye fixation; facial expression; female; human; male; masking; noise; photostimulation; preschool child; speech; speech audiometry; speech perception; videorecording; vision; voice; young adult

Strain-specific programming of prenatal ethanol exposure across generations. - Popoola, Daniel O; Nizhnikov, Michael E; Cameron, Nicole M (Alcohol (Fayetteville, N.Y.), 2017)
Behavioral consequences of prenatal alcohol exposure (PAE) can be transmitted from in utero-exposed F1 generation to their F2 offspring. This type of transmission is modulated by genetic and epigenetic mechanisms. This study investigated the intergenerational consequences of prenatal exposure to a low ethanol dose (1 g/kg) during gestational days 17-20, on ethanol-induced hypnosis in adolescent male F1 and F2 generations, in two strains of rats. Adolescent Long-Evans and Sprague-Dawley male rats were tested for sensitivity to ethanol-induced hypnosis at a 3.5-g/kg or 4.5-g/kg ethanol dose using the loss of righting reflex (LORR) paradigm. We hypothesized that PAE would attenuate sensitivity to ethanol-induced hypnosis in the ethanol-exposed animals in these two strains and in both generations. Interestingly, we only found this effect in Sprague-Dawley rats. Lastly, we investigated PAE related changes in expression of GABAA receptor alpha1, alpha4, and delta subunits in the cerebral cortex of the PAE sensitive Sprague-Dawley strain. We hypothesized a reduction in the cerebral cortex GABAA receptor subunits' expression in the F1 and F2 PAE groups compared to control animals. GABAA receptor alpha1, alpha4, and delta subunits protein expressions were quantified in the cerebral cortex of F1 and F2 male adolescents by western blotting. PAE did not alter cerebral cortical GABAA receptor subunit expressions in the F1 generation, but it decreased GABAA receptor alpha4 and delta subunits' expressions in the F2 generation, and had a tendency to decrease alpha1 subunit expression. We also found correlations between some of the subunits in both generations. These strain-dependent vulnerabilities to ethanol sensitivity, and intergenerational PAE-mediated changes in sensitivity to alcohol indicate that genetic and epigenetic factors interact to determine the outcomes of PAE animals and their offspring. Copyright © 2017 Elsevier Inc. All rights reserved.
9 citations (Crossref) [2023-10-31] Place: United States Popoola, Daniel O. Psychology Department, Center for Developmental and Behavioral Neuroscience, Developmental Exposure Alcohol Research Center, Binghamton University- SUNY, 4400 Vestal Parkway East, Binghamton, NY 13902, USA. Nizhnikov, Michael E. Southern Connecticut State University, 501 Crescent Street, New Haven, CT, 06515-1355, USA. Cameron, Nicole M. Psychology Department, Center for Developmental and Behavioral Neuroscience, Developmental Exposure Alcohol Research Center, Binghamton University- SUNY, 4400 Vestal Parkway East, Binghamton, NY 13902, USA. Electronic address: ncameron@binghamton.edu.
Keywords: *Alcohol Drinking/ae [Adverse Effects]; *Behavior; Animal/de [Drug Effects]; *Cerebral Cortex/de [Drug Effects]; *Ethanol/to [Toxicity]; *Prenatal Exposure Delayed Effects; *Receptors; GABA-A/de [Drug Effects]; 4 aminobutyric acid A receptor; 4 aminobutyric acid A receptor alpha1; 4 aminobutyric acid A receptor alpha4; Age Factors; Alcohol Drinking; Alcohol Drinking/ge [Genetics]; Alcohol Drinking/me [Metabolism]; Alcohol Drinking/px [Psychology]; Animals; Article; Behavior; Animal; Blood Alcohol Content; Cerebral Cortex; Cerebral Cortex/me [Metabolism]; Cerebral Cortex/pa [Pathology]; Dose-Response Relationship; Drug; Epigenesis; Genetic; Epigenesis; Genetic/de [Drug Effects]; Ethanol; Ethanol/bl [Blood]; Female; Gestational Age; Long Evans rat; Male; Maternal Exposure; Pregnancy; Prenatal Exposure Delayed Effects; Rats; Long-Evans; Rats; Sprague-Dawley; Reaction Time; Receptors; GABA-A; Receptors; GABA-A/ge [Genetics]; Receptors; GABA-A/me [Metabolism]; Reflex; Righting; Reflex; Righting/de [Drug Effects]; Species Specificity; Sprague Dawley rat; Time Factors; Western blotting; adolescent; adult; age; alcohol; alcohol blood level; alcohol consumption; animal; animal behavior; animal experiment; animal model; animal tissue; blood; brain cortex; comparative study; controlled study; correlational study; dept.psy; dose response; drinking behavior; drug effects; epigenetics; female; genetic epigenesis; genetics; gestation period; gestational age; hemoglobin delta chain; heredity; hypnosis; male; maternal exposure; metabolism; nonhuman; outcome assessment; pathology; peer-reviewed; pregnancy; prenatal exposure; progeny; protein expression; psychology; rat

Audiovisual speech perception: A new approach and implications for clinical populations - Irwin, Julia; DiBlasi, Lori (Language and Linguistics Compass, 2017)
This selected overview of audiovisual (AV) speech perception examines the influence of visible articulatory information on what is heard. Thought to be a cross-cultural phenomenon that emerges early in typical language development, variables that influence AV speech perception include properties of the visual and the auditory signal, attentional demands, and individual differences. A brief review of the existing neurobiological evidence on how visual information influences heard speech indicates potential loci, timing, and facilitatory effects of AV over auditory only speech. The current literature on AV speech in certain clinical populations (individuals with an autism spectrum disorder, developmental language disorder, or hearing loss) reveals differences in processing that may inform interventions. Finally, a new method of assessing AV speech that does not require obvious cross-category mismatch or auditory noise was presented as a novel approach for investigators.
9 citations (Crossref) [2023-10-31]
Keywords: dept.psy

Teaching and learning guide for audiovisual speech perception: A new approach and implications for clinical populations. - Irwin, Julia; Turcios, Jacqueline (Language and linguistics compass, 2017)
0 citations (Crossref) [2023-10-31] Place: England Irwin, Julia. Haskins Laboratories, New Haven, CT, USA. Irwin, Julia. Southern Connecticut State University, New Haven, CT, USA. Turcios, Jacqueline. Haskins Laboratories, New Haven, CT, USA. Turcios, Jacqueline. Southern Connecticut State University, New Haven, CT, USA.
Keywords: dept.psy